The future of personalized medical nutrition; a focus on protein - Smeets, Rolf (World Nutrition Journal, 2025)
Dietary protein is essential for preserving muscle mass and preventing adverse outcomes in a wide range of patient populations. However, achieving sufficient protein intake remains a major challenge, particularly in disease states where requirements are elevated—often double the normal needs—while intake is impaired